Pengaruh Terapi Moxa Mugwort terhadap Durasi Persalinan Ibu Inpartu Kala 1 - Alda Alvian Ningrum; Rosyidah Alfitri (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Introduction Maternal Mortality Rate (MMR) is one of the indicators to determine the quality of maternal health services in Indonesia. Obstetric complications greatly affect MMR, including long first stage of labor. Moxa therapy is a traditional therapy that uses mugwort plants (artemisia vulgaris) to provide warmth to acupuncture points in the body. The goal is to stimulate energy circulation (QI) and blood. Method This study aims to determine the differences before and after intervention related to the duration of labor of inpartu mothers after giving mugwort moxa. This study is a pre-experimental study with a one group pretest-posttest study design conducted on inpartu mothers in the first stage. Results The calculated value obtained from the calculation using the T-test was 0.015, so the calculated t value <0.05 (0.15 <0.05) so it can be said that moxa therapy affects the duration of the first stage of labor. The conclusion of this study is that there is a significant relationship between mugwort moxa therapy and the duration of labor of inpartu mothers in the first stage of labor at the Malang Regional Health Facility. Mugwort moxa therapy tends to shorten the duration of the first stage of labor.